An observation of seating provision and users’ behaviour in the regional shopping complexes in Kuala Lumpur, Malaysia - Denan, Zuraini; Che Hasim, Nor Dalila Nazihah; Abdul Rahim, Zaiton (2013)

(untitled)
Increasing numbers of shopping complex development in Malaysia, especially in Kuala Lumpur were obviously seen for the past 10 years. Big shopping complexes seem to attract lots of visitors due to their commercial variations and outlook images. The bigger the shopping complex, the longer time-spend at the shopping complexes. Conveniences to shop and rest were major factors in influencing the mood to shop, to enjoy leisure activities or just window shopping. As shopping complexes becoming most frequently visited places in urban area, comfort has become an important issue. Comfort on seating facilities has become an issue to shoppers, at regional size shopping complexes. Investigation on seating provision require further research to ensure shoppers are comfortable and will attracted to visit the shopping complex frequently. Thus, the paper presents a finding on the observation of seating provision and its impact on the shoppers’ behavior. The consideration of few aspects of seating such as type, arrangement, location, material and number of seating has been identified. The research found that the aspects of seating at three selected shopping complexes meet the users’ satisfaction level. However, total number of seating at Suria KLCC is inadequate as compared to One Utama Shopping Center and Mid Valley Megamall. Based on the findings also, seating is in need due to the activities done in shopping complexes which is related to the users’ duration of stay. Consideration on the provision of seating seems to have positive feedback by the users’ thus it enhances the business and benefited the shopping complexes management.